Afterglow of Empire: Egypt from the Fall of the New Kingdom to the Saite Renaissance - Dodson, Aidan (The American University in Cairo Press, 2019)
From the eleventh through the sixth centuries BC, the power and the glory of the imperial pharaohs of Egypt's New Kingdom crumbled in the face of internal crises and external pressures, ultimately reversed by invaders from Nubia and consolidated by natives of the Nile Delta following a series of Assyrian invasions. Much of this era remains obscure, with little consensus among Egyptologists. Aidan Dodson reconsiders the evidence and proposes a number of new solutions to the problems of the period. He also considers the era's art, architecture, and archaeology, including the royal tombs of Tanis.